2018
DOI: 10.3390/medicines5010005
|View full text |Cite
|
Sign up to set email alerts
|

Sino-Austrian High-Tech Acupuncture Network: Annual Report 2017

Abstract: The Sino-Austrian High-Tech Acupuncture Research Network was founded in 2005 and has been growing ever since. The network comprises many partners from China and is highly involved in research and education activities. This report introduces the network’s activities in the year 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…It is natural to resort to robots to perform acupuncture work for their precision and endurance. According to the published research, the earliest idea about acupuncture robot was mentioned as high-tech acupuncture by Gerhard Litscher of Medical University of Graz in1997 [ 1 ]. More than twenty years ago, when the research team at the Medical University of Graz, in 1997, showed that acupuncture also works in the electronics laboratory without the aid of an acupuncturist and when they introduced the term computer-controlled acupuncture [ 2 ], they did not use the term meaning that the computer replaces the acupuncturist; they rather understood the quantification of measurable effects of acupuncture [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is natural to resort to robots to perform acupuncture work for their precision and endurance. According to the published research, the earliest idea about acupuncture robot was mentioned as high-tech acupuncture by Gerhard Litscher of Medical University of Graz in1997 [ 1 ]. More than twenty years ago, when the research team at the Medical University of Graz, in 1997, showed that acupuncture also works in the electronics laboratory without the aid of an acupuncturist and when they introduced the term computer-controlled acupuncture [ 2 ], they did not use the term meaning that the computer replaces the acupuncturist; they rather understood the quantification of measurable effects of acupuncture [ 3 ].…”
Section: Introductionmentioning
confidence: 99%